Incorporating corpus linguistics in the development of vocabulary and phraseological index / Wong Wei Lun, Warid Mihat and Mairas Abdul Rahman - Wong, Wei Lun; Mihat, Warid; Abdul Rahman, Mairas (Universiti Teknologi MARA, 2024)
This study highlighted the need for developing teaching and learning resources in this 21st century, especially in language learning. Hence, this study presented a contemporary method that combined corpus linguistics with developing a vocabulary and phraseological index. The aim was to improve the learning of English at all levels of education. Selecting a doctoral study as a reference, this study demonstrated the practical implementation of corpus linguistics integrating SkecthEngine. A substantial dataset involving 560 extended writing, amounting to 152,187 words, formed the basis for computational analysis. This analysis presented a list of twenty salient vocabulary and phrases, categorised by their literary genre and corresponding to the levels of the CEFR. Concordances were employed to display authentic example sentences. Finally, the vocabulary and phraseological index provided a convenient and valuable resource for language teachers, tailored to different educational settings.